2017
DOI: 10.1093/nar/gkx442
|View full text |Cite
|
Sign up to set email alerts
|

Replication studies of carboxymethylated DNA lesions in human cells

Abstract: Metabolic activation of some N-nitroso compounds (NOCs), an important class of DNA damaging agents, can induce the carboxymethylation of nucleobases in DNA. Very little was previously known about how the carboxymethylated DNA lesions perturb DNA replication in human cells. Here, we investigated the effects of five carboxymethylated DNA lesions, i.e. O6-CMdG, N6-CMdA, N4-CMdC, N3-CMdT and O4-CMdT on the efficiency and fidelity of DNA replication in HEK293T human embryonic kidney cells. We found that, while neit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…O 4 -carboxymethylthymidine ( O 4 -CMdT) is a strong replication block (51%) and very mutagenic, causing 86% T>C mutation [36]. N 3 -CMdT, O 4 -CMdT and O 6 -carboxymethyl-dG ( O 6 -CMdG) moderately block DNA replication in human cells [48]. N 3 -CMdT causes T>A (81%) mutation; O 4 -CMdT causes T>C (68%) mutation; O 6 -CMdG causes G>A (6.4%) mutation; neither N 6 -CMdA nor N 4 -CMdC block replication or induce mutation [48].…”
Section: Discussion On Individual Modificationsmentioning
confidence: 99%
“…O 4 -carboxymethylthymidine ( O 4 -CMdT) is a strong replication block (51%) and very mutagenic, causing 86% T>C mutation [36]. N 3 -CMdT, O 4 -CMdT and O 6 -carboxymethyl-dG ( O 6 -CMdG) moderately block DNA replication in human cells [48]. N 3 -CMdT causes T>A (81%) mutation; O 4 -CMdT causes T>C (68%) mutation; O 6 -CMdG causes G>A (6.4%) mutation; neither N 6 -CMdA nor N 4 -CMdC block replication or induce mutation [48].…”
Section: Discussion On Individual Modificationsmentioning
confidence: 99%
“…25 Therefore, the data suggested an involvement of TLS Pols κ and ζ in error-free bypass of O 6 -CMG whereas Pol ι seems to be responsible for the mutagenic bypass of the adduct. 25 In line with these findings, primer extension experiments demonstrated that the replicative Pol δ was only moderately blocked. Additionally, Pol κ, which only inserted dCTP, was the highest fidelity Pol amongst the TLS Pols tested, 26 and Pols η and ι frequently misincorporated dATP and dTTP opposite O 6 -CMG.…”
Section: Introductionmentioning
confidence: 89%
“…In HEK293 cells transfected with plasmids containing a site-specific O 6 -CMG, the adduct was a modest block for DNA synthesis and was moderately mutagenic. 25 Adduct bypass decreased in cells deficient in Pol κ and ζ and O 6 -CMG induced exclusively GCAT mutations at a frequency of 6.4% when Pol ι was genetically depleted. 25 Therefore, the data suggested an involvement of TLS Pols κ and ζ in error-free bypass of O 6 -CMG whereas Pol ι seems to be responsible for the mutagenic bypass of the adduct.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations